Legal Consequences of Land Sale and Purchase Transactions Based on Receipts on Land Ownership Rights - Roslina Mantolongi; Weny Almoravid Dungga; Sri Nanang Meiske Kamba (The Easta Journal Law and Human Rights, 2026)
This study examines the legal consequences of land sale and purchase transactions based on receipts on ownership rights within the Indonesian agrarian legal system. The main issue lies in the practice of the community, which still uses receipts as the basis for transactions without fulfilling the formal procedures established by law. This study aims to analyze the evidentiary weight of receipts and their implications for the legal certainty and protection of land rights. The method used is normative legal research employing a legislative, conceptual, and case-based approach, through a literature review of primary and secondary legal sources. The results of the study indicate that a receipt only serves as evidence of payment and cannot legally prove the transfer of land rights. Consequently, transactions based on receipts do not provide legal certainty and have the potential to lead to disputes. In conclusion, the transfer of land rights must meet formal requirements through an authentic deed and land registration to ensure legal certainty and the protection of rights.